2020
DOI: 10.3390/ijms21186469
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training and Vitamin C Supplementation Affects Ferritin mRNA in Leukocytes without Affecting Prooxidative/Antioxidative Balance in Elderly Women

Abstract: Physical training and antioxidant supplementation may influence iron metabolism through reduced oxidative stress and subsequent lowering of mRNA levels of genes that are easily induced by this stress, including those responsible for iron homeostasis. Fifteen elderly women participated in our 12-week experiment, involving six weeks of training without supplementation and six weeks of training supported by oral supplementation of 1000 mg of vitamin C daily. The participants were divided into two groups (n = 7 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Recently, we investigated changes in expression of genes associated with iron metabolism, which is also easily induced by oxidative stress in elderly women (part of a wider project on vitamin C supplementation during health training). We concluded that vitamin C supplementation caused a decrease in ferritin mRNA [3]. Indirectly these ndings indicate that vitamin C supplementation decreased intracellular free iron and consequently oxidative intracellular status.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Recently, we investigated changes in expression of genes associated with iron metabolism, which is also easily induced by oxidative stress in elderly women (part of a wider project on vitamin C supplementation during health training). We concluded that vitamin C supplementation caused a decrease in ferritin mRNA [3]. Indirectly these ndings indicate that vitamin C supplementation decreased intracellular free iron and consequently oxidative intracellular status.…”
Section: Introductionmentioning
confidence: 65%
“…The protocol used for gene expression evaluation has been previously described in detail by Grzybkowska [26], Żychowska [3]. Brie y, 2 ml of venous blood was collected and to remove red blood cells, the Red Blood Cell Lysis Buffer (RBCL) (A&A Biotechnology, Gdynia, Poland) was added and the samples were then centrifuged.…”
Section: Genetic Evaluationmentioning
confidence: 99%
See 3 more Smart Citations